A Charmed Journey into the Land of Spirit Medium - Chai, Elena Gregoria Chin Fern (Strategic Information and Research Development Centre, 2018)
The author shares her personal experience in conducting fieldwork from a small town in Laos, bordering Vietnam to her PhD fieldwork in the new village in Sarawak. She then described her serendipty destiny into the world of Chinese deities and temples in Sarawak and way over the border of West Kalimantan. For her, doing ethnography is akin to living life. It is never finished and we can never quite make sense of our own lives. The people we meet, the experiences we encounter are condiments to life.